Alasan Indonesia Tidak Meratifikasi The Regional Cooperation Agreement on Combating Piracy and Armed Robbery Against Ships in Asia (ReCAAP) - Achmad Ismail (Jurnal Alternatif - Jurnal Ilmu Hubungan Internasional, 2022)
The Vision of President Jokowi to create Indonesia as world maritime axis meets variety of challenges. Piracy and armed robbery are the real threat faced by each state, in particular Indonesia as maritime (archipelagic) state. The escalation more be realized in real life. For facing the challenges, states in Asia create The Regional Cooperation Agreement on Combating Piracy and Armed Robbery Against Ships in Asia (ReCAAP). Unfortunately, Indonesia is not joined into that regional cooperation that makes this phenomenon is very interesting to investigate. Therefore, this article aimed to understand the reason of Indonesia is not ratify ReCAAP using Foreign Policy concept that popularized by James Rosenau is needed as “knive of analysis”. The writing begins with a condition piracy and armed robbery in region of Asia, in particular Indonesia, followed by an exposure foreign policy concept from James Rosenau, discussion from (systemic, societal, governmental & idiosyncratic sources) that causing foreign policy of Indonesia is not ratify ReCAAP.